The new arts entrepreneur : navigating the arts ecologies - Beckman, Gary D., 1961- (Abingdon, Oxon ; New York : Routledge, 2021)
"The New Arts Entrepreneur is the first uniquely designed pedagogy for arts entrepreneurship educators and students. Melding an arts-first approach with understandable entrepreneurial concepts and newly formulated tools, the text helps arts students to envision themselves as an entrepreneurial CEO, not simply another random entrepreneur flailing through a maze of well-worn entrepreneurial suggestions that don't fit. At the core of the text is the Entrepreneurial Ecologies of the Arts. The Ecologies provide a framework to envision an entrepreneurial horizon for almost any arts-based business, included those ventures seeking to impact the production of art. In addition to this revolutionary framework, the text also introduces tools designed to compliment the Ecologies. Designed with arts students in mind, it accomplishes two critical tasks not found in other textbooks: venture sustainability and decision-making. This newly developed approach focuses on the decision-making required to sustain new arts ventures and will be of interest to arts students from all disciplines"--
Setting the stage -- Fundamental concepts and definitions -- Starting an arts business and economics for artists -- The entrepreneurial ecology of the arts -- Using the entrepreneurial ecology of the arts -- Advanced ecologies -- Tools.
OCLC-licensed vendor bibliographic record.
Keywords: Arts -- Economic aspects; Arts -- Vocational guidance; BUSINESS & ECONOMICS -- General; BUSINESS & ECONOMICS -- Entrepreneurship; BUSINESS & ECONOMICS -- Small Business